Real Earnings Management: Study on Manufacturing Sector - Rezki Zurriah; Masta Sembiring; Siti Aisyah Siregar (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
The objective of research was to analyze the influence of the firm size, leverage, profitability, sales growth and free cash flow on real earnings management in companies manufacturing sector listed on the Indonesia Stock Exchange in the period of 2016 – 2020. The samples were 124 companies taken by using purposive sampling technique for the population of 193 companies at the total observation of 620 analytical units. Secondary data were gathered by conducting documentary studies such as annual financial and annual financial statements published on the websitewww.idx.co.id. The gathered data were analyzed by using panel data regression analysis. The results of the research showed that firm size, leverage, profitability, sales growth and free cash flow had a significant influence on real earnings management. Partially, firm size and profitability had a negative significant influence on real earnings management, while leverage and sales growth did not have any significant influence on real earnings management but free cash flow had a positive significant influence on real earnings management.